Prevalence and Public Perception on Causes of Paedophilia in Osun State Nigeria - Oluwatosin, S. A.; Akinbo, Oluwaseun Tope (Advances in Social Sciences Research Journal, 2017)
This study assessed the prevalence and the predisposing factors on pedophilic occurrence and, furthermore examines the public perception on ways of preventing it. The study adopted the survey research design. The sample comprised of 1200 respondents which includes, teachers in both private and public schools, church members, mosque members, civil servants and traders/artisans adults between the ages of 18 years and above, both educated and uneducated. Three senatorial district were selected from the state, and from each of the senatorial district one Local Government Areas (LGAs) was selected using simple random sampling technique making a total of three LGAs. From each of the LGAs 400 adults were selected between the ages of 18years and above. Ask instrument, Questionnaire on pedophilic occurrence (QPO) was used to collect information from the respondents it was divided into three sections and titled prevalence of pedophilia occurrence (PPO). Predisposing factors pedophilic occurrence (PPPF). Perceived measures of preventing pedophilia (PMPP). Data collected were analyzed using frequency counts, simple percentages and chi-square. The results showed that the prevalence of pedophilic occurrence in the respondents environment is 24.7% and knowledge of pedophilia occurrence is also low (27.11): Factors that influence pedophilia occurrence include, social media, family background, loneliness, pornography, sexually deprived partner, sexually abused, not reporting of offenders, low self-esteem, depression, health problem and social economic factor, these factors are arranged in order of influence. There was significant influence of some of the predisposing factors (social, media, pornography, sexually deprived, sexually abused No reporting of offender, family background) on the occurrence of pedophilia. The study concluded that since the knowledge of pedophilia occurrence is low in the respondent Environment. The public needs to be educated on what pedophilia is and what to be done when such occurs, and also the need for reporting when such occurs.